Educational Process Followed in Street Classrooms - RAJPUT, GUNJAN (THE PRIMARY TEACHER, 2015)
The educational process followed in formal school classrooms is different from the process followed in the classrooms of non-formal educational programmes where the certificate and validity of learning is not assured. One such programme operating in India is Mobile School Programme. The objective of the paper is to assess as how the educational process takes place inside the classrooms of the mobile school programmes, which is assessed on the basis of teaching-learning activities generally liked by children, child friendliness of the classroom and student evaluation adopted by teachers in the classrooms. Four NGOs are running Mobile Schools and cover 18 slums of Delhi. The analysis is based on the data collected through direct observation by the researcher in the classrooms.